The supervised internship in visual arts as a research field in teacher education (Revista Apotheke, 2022)
This writing intends to expand the possibilities of understanding the supervised internship, beyond the moment of teaching practice, perceiving it as a field of research in teacher training and artistic poetics. The writing reviews the literature on supervised internship in visual arts in Oliveira (2013), Oliveira and Lampert (2010), and Pimenta and Lima (2005/2006). Thus, it analyzes the role of the curricular internship in undergraduate courses, as well as aims to contribute to the construction of teaching identity, in the training of researchers and artist-teachers, as it understands the supervised internship as a place of teaching practice, research and artistic poetics.
Keywords: Supervised internship; Visual arts; Teaching training